Hybrid Surfactants with N‐Heterocyclic Carbene Heads as a Multifunctional Platform for Interfacial Catalysis. Issue 72 (18th October 2017) - Donner, Adrian; Hagedorn, Kay; Mattes, Lorenz; Drechsler, Markus; Polarz, Sebastian
Abstract: Processing of substrates with different solvent compatibility is a persistent problem in homogeneous catalysis, in particular when one starting compound is water soluble and the other is not. A promising concept reported in the literature is micellar catalysis. However, the process of developing catalysts that are surfactants at the same time is still in its early stages. We report the synthesis of a new surfactant system with an N ‐heterocyclic carbene (NHC) moiety as a head group. Characteristic surfactant properties such as the formation of micelles or liquid crystals is documented. The new surfactant ligand forms coordination compounds with various metals, most importantly Pd 2+, in square planar geometry. In addition, the Pd‐NHC compound shows surfactant features, and can be used successfully for C−C cross‐coupling reactions (Suzuki, Heck). The boost in catalytic activity by one order of magnitude compared to analogous but non‐amphiphilic species is reported. Abstract : Soapy catalyst in action : An organic–inorganic hybrid surfactant containing a carbene‐Pd complex as a head is used for micellar catalysis bridging the gap for substrates with orthogonal solvent‐compatibility (see figure).